2022
DOI: 10.1007/s12144-022-02925-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethical leadership: Exploring bottom-line mentality and trust perceptions of employees on middle-level managers

Abstract: With the increased competitiveness and significance of the workforce, the responsibility of organizational leaders has been increased to behave ethically and lead their followers in the best ethical way. This study aims to explore how the perception and trust of followers of their middle-level managers can shape the ethical behavior of middle managers and their bottom-line mentality. This qualitative study was conducted using semi-structured interviews from 10 employees of two Pakistani textile organizations—s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The authors suggested that the incongruity between leader and employee BLM provoked a stronger, negative relationship with LMX that resulted in even lower employee performance. Also, relying on leader-member exchange arguments, a qualitative study suggested that top management BLM can affect supervisors' interpretations of work tasks as being difficult, as well as supervisors' poor attitudes, with the downstream effects of provoking supervisors' social undermining behaviors and decreasing their ethical leadership (Malik et al, 2022).…”
Section: An Overview Of Leader Blmmentioning
confidence: 99%
“…The authors suggested that the incongruity between leader and employee BLM provoked a stronger, negative relationship with LMX that resulted in even lower employee performance. Also, relying on leader-member exchange arguments, a qualitative study suggested that top management BLM can affect supervisors' interpretations of work tasks as being difficult, as well as supervisors' poor attitudes, with the downstream effects of provoking supervisors' social undermining behaviors and decreasing their ethical leadership (Malik et al, 2022).…”
Section: An Overview Of Leader Blmmentioning
confidence: 99%
“…A leader who embodies social responsibility is one who is sincere, compassionate, transparent, and supportive of two-way communication. Socially responsible leaders reassure their followers that looking out for the best interests of their staff is their top priority (Malik et al, 2023). Based on Bandura's (1977) social learning theory, earlier research has demonstrated that followers tend to learn from and attempt to imitate the actions of socially responsible leaders (Kyambade et al, 2023a) because they are viewed as role models.…”
Section: Psychological Safety As a Mediatormentioning
confidence: 99%
“…In summary, existing work on BLM has emphasized that BLM results in certain outcomes because of a "neglect of competing priorities," which is a central aspect of the BLM concept (Babalola et al, 2020;Greenbaum et al, 2012). To sum up, in today's business environment, the BLM is increasing; however, its consequences on leader-follower relationships are yet to be studied (Greenbaum et al, 2020a(Greenbaum et al, , 2020bMalik et al, 2022). Specifically, work on BLM has yet to examine the role of social rank within the group and other performance domains such as knowledge management.…”
Section: Existing Research On Bottom-line Mentalitymentioning
confidence: 99%
“…In the workplace, leaders have great influence on employees within organizational settings (Malik et al, 2022), especially under the context of Chinese culture, in which strict hierarchy and active implementation among the upper and lower levels are emphasized. For example, leaders have considerable executive power requirements with which to control the behavior of subordinates (Zhang et al, 2021).…”
Section: Existing Research On Bottom-line Mentalitymentioning
confidence: 99%